The Level of Heat Shock Protein 70 is Lower in Postterm Pregnancy - Soetrisno, Soetrisno (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To analyze whether there are differences between the levels of HSP70 of Postterm pregnancy and aterm pregnancy in Dr. Moewardi Hospital, Surakarta, Central Java. Method: This was a cross-sectional study. The independent variable was the level of Heat Shock Protein 70 (HSP70), and the dependent variable was the incidence of postterm pregnancy. The data was then analyzed by t test. Result: The subjects were 45 women, who were divided into 2 groups of women with postterm pregnancies (15 women) and aterm pregnancies (30 women). The mean levels of HSP70 in the serum of women with postterm pregnancy is lower (0.40 ng/ml) compared to the level of the normal pregnant group (3.94 ng/ml) and this difference was statistically significant (p